An electrodeposited amorphous cobalt sulphide nanobowl array with secondary nanosheets as a multifunctional counter electrode for enhancing the efficiency in a dye-sensitized solar cell. (20th November 2019) - Jiang, Qing-Song; Cheng, Wenjie; Wu, Jing; Li, Wenbo; Yan, Keyou
Abstract: Light trapping by the ordered nanostructure of a photoanode has been considered to be an effective way to improve the photovoltaic performance of a dye-sensitized solar cell (DSSC), but it is rarely reported for the counter electrode. In the present work, a two-dimensional cobalt sulphide (Co-S) nanobowl array with a hierarchical structure has been designed for the counter electrode with a light scattering effect and fabricated by a potential reversal electrodeposition technique. The Co-S nanobowl array is amorphous with secondary nanosheets. Due to lattice distortions and more edge-sites with dangling bonds, the amorphous phase increases the catalytic activity for electrolyte regeneration. Additionally, the Co-S nanobowl array with ordered hierarchical pores is beneficial for the diffusion of the I − /I3 − redox couples. The DSSC assembled with Co-S nanobowl array exhibits excellent photovoltaic performance with a champion power conversion efficiency (PCE) as high as 7.78%, which is larger than those of DSSC assembled with Pt (6.51%) and Co-S (7.14%) counter electrodes. Hence, the Co-S nanobowl array is a multifunctional counter electrode for superior electrocatalytic performance and light scattering effect. Graphical abstract: A two-dimensional amorphous Co-S nanobowl array with a hierarchical structure exhibits excellent electrocatalytic activity, and the photovoltaic performance of the corresponding dye-sensitized solar cell is improved from 6.51% to 7.78% compared with a conventional Pt-based device.Image 1 Highlights: Amorphous Co-S nanobowl array is fabricated by an electrodeposition technique. The amorphous and hierarchical structure increase electrocatalytic active sites. Hierarchical structure provides more diffusion channels for I − /I3 − redox couple. The light absorption of the photoanode is enhanced by the light scattering effect. As counter electrode, Co-S nanobowl array exhibits superior performance to platinum.